Property Rights and Bijuralism Can a Framework for an Efficient Interaction of Common Law and Civil Law Be an Alternative to Uniform Law? - Bornheim, Jan Jakob (Mohr Siebeck, 2020)
Using the Canadian experience as a model, Jan Jakob Bornheim shows that the efficient interaction of common law and civil law can take place on both vertical and horizontal planes.
PublicationDate: 20201022
Keywords: Comparative Law -- Kommunalverfassung -- marginof appreciation -- Legal Theory -- indirekte Steuerung -- pietistischer Separatismus -- Property Law -- Conflict of Laws -- Rechtstheorie -- Bürgerliches Recht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Internationales Privatrecht -- Ausländisches Recht, Rechtsvergleichung